Online communication strategy of world political leaders during the Ukraine crisis (February 24 - December 24, 2022). Comparative case study: Joe Biden, Ursula von der Leyen and Jens Stoltenberg - Tasenţe, Tănase (Technium Social Sciences Journal, 2023)
This case study looks at the online communication strategies of three prominent world political leaders during the Ukraine crisis in February-December 2022. Using the case studies of U.S. President Joe Biden, European Commission President Ursula von der Leyen, and NATO Secretary General Jens Stoltenberg, this study examines how the three leaders used online communication tools to shape their respective strategies and communicate their messages to the international community. Through an in-depth analysis of each leader's approach to online communication, the study reveals how the three leaders used varying levels of engagement, commentary, and content to project strength, unity, and stability during a time of significant international tension. It also highlights how each leader used different strategies to reach and engage a global audience, indicating a clear need to understand the nuances of online communication to successfully navigate complex global crises. The study ultimately suggests that strategic use of online communication can be a powerful tool for world leaders in times of international crisis.